English Performance of the Students of the English Department from Different Educational Backgrounds - Sakinah Aprilia Dewi; Ali Saukah; Utari Praba Astuti (Jurnal Pendidikan Humaniora, 2021)
Abstract: This study aimed to compare school program attended by students in Senior High School based on the score of the English performance. The data collected were in form of participants’ individual score of Placement test. The data representing 309 participants divided in to three groups; natural science, social science and language program. English performance score obtained from placement test of intensive course program was analysed using one way analysis of variance (ANOVA) The result shows that Students with language program backgrounds outscore students with a social science program but not better than students with natural science program.Keywords: educational backgrounds, english performance, natural science, social scienceLanguage ProgramAbstrak: Penelitian ini bertujuan untuk membandingkan program sekolah yang diambil  siswa di Sekolah Menengah Atas berdasarkan nilai bahasa Inggris. Data yang dikumpulkan adalah dalam bentuk nilai masing-masing mahasiswa dari tes Penempatan. Data yang mewakili 309 peserta dibagi menjadi tiga kelompok; ilmu pengetahuan alam, ilmu pengetahuan sosial dan program bahasa. Nilai bahasa Inggris yang diperoleh dari tes penempatan program Intensive Course dianalisis menggunakan analisis varians satu arah (ANOVA). Hasilnya menunjukkan bahwa siswa dengan latar belakang program bahasa mengungguli siswa dengan program ilmu pengetahuan sosial tetapi tidak lebih baik daripada siswa dengan program ilmu pengetahuan alam.Kata kunci: latar belakang pendidikan, kinerja bahasa Inggris, ilmu alam, ilmu sosial